ESL And ASL Students’ and Teachers’ Perspectives On Online Classroom Management Techniques - Kareema, Mohamed Ismial Fouzul; Hakmal, M.H.M. (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Classroom management is an essential concept in the implementation of the learning process in the classroom. The successful execution of effective classroom management is a significant factor in determining the future viability of education, specifically through a virtual learning environment where physical interaction is lacking. The primary objective of the study is to investigate English as a Second Language (ESL) and Arabic as a Second Language (ASL) students' and teachers’ perceptions of implementing classroom management techniques via online learning platforms and to analyze the effectiveness and different kinds of classroom management techniques implemented via online learning platforms. The study adopted a mixed method in which questionnaires were distributed to all 40 ESL and ASL students to collect numerical data. 20 students and 10 lecturers involved in teaching and learning ESL and ASL were interviewed to collect the potential impact of using classroom management techniques. The study's significant findings revealed that many dynamic classroom management techniques have been incorporated to ensure a positive learning environment, eradicate disruptive behaviours, active participation, and better learning outcomes. Furthermore, dynamic classroom management techniques and online classroom ethics have been proposed to ensure better learning outcomes online.